Bottom up Treatment for Vulvar and Lower Extremity Varicose Veins of Pelvic Origin: A Case Report - Aleksandra Jaworucka-Kaczorowska; Marianne De Maeseneer (EJVES Vascular Forum)
Background: Extrapelvic varices of pelvic origin, such as vulvar varices, and lower extremity varicose veins (VVs) of pelvic origin are being diagnosed with increasing frequency. A proper management strategy, including history, physical examination, duplex ultrasound (DUS) of the lower extremities, DUS of pelvic escape points, selection of appropriate treatment, and post-treatment care, is essential for good patient outcomes and satisfaction. Case report: A non-pregnant, 27 year old female presented with prominent vulvar varices in combination with right sided VVs on the anterior and medial thigh, calf, and buttock. She was successfully managed by bottom up treatment with ultrasound guided foam sclerotherapy. The bottom up technique involves treatment of VVs of pelvic origin by direct puncture of the pelvic escape points and associated VVs, without embolisation of the pelvic veins. Conclusion: This case illustrates successful bottom up treatment in accordance with recent guidelines in a female patient with extensive VVs of pelvic origin.